An investigation of liquid coating via the contact spreading mechanism in tumbling drum and fluidised bed coating processes - Norzaida Yusof
The spray coating of particles is used in many industrial applications. One of the mechanisms involves the transfer of liquid between particles via liquid bridge formation and rupture; known as contact spreading. To date, there has been limited research into this mechanism. Indeed, the few studies reported have only been theoretical or modelling based. In this thesis, a first experimental approach focusing on the liquid contact spreading mechanism is presented. Experimental data has been used to describe and quantify this mechanism, and this work will contribute to the design and scale-up of coating processes. Two coating techniques, commonly used in industry, have been employed for this study; tumbling drum and fluidised bed. Experiments were conducted using model materials; spherical alumina particles and aqueous polymer solutions as the coating liquids with varying viscosities. For these studies, specially designed experiments were conducted to study the contact spreading mechanism only. Of particular importance was the degree of coating uniformity within a batch of particles, quantified by the inter-particle coating variability (Co V). A new image analysis system, based on colorimetric measurement, has been developed to quantitatively determine the colour uniformity of particles coated with dyed solutions. Here, it is demonstrated that this novel method can analyse a large number of particles in a relatively small period of time and gives reproducible data with which to determine the Co V of a batch. Contact spreading was seen to occur in all systems studied. This supports the concept that contact spreading plays an important role in the spray coating process. Indeed, in the both tumbling drum and the fluidised bed system under certain conditions, a near-uniform coating was ultimately achieved. The rate of contact spreading and, therefore, the time to complete the coating process, was highly dependent on both formulation and operational parameters. For example, the lower the coating liquid viscosity, the faster the rate of contact spreading. An increase in tumbling speed in the drum and fluidisation velocity in the fluidised bed also resulted in an increase in contact spreading rate. The method of liquid addition in the fluidised bed was also found to affect the contact spreading process. The findings are attributed to differences in the formation and rupture of liquid bridges between particles which influence the extent of liquid transfer via contact spreading. This study has demonstrated that the viscous Stoke number, tv, and the critical Stokes number, St-, as a function of collision velocity can be applied to predict the sticking criterion of the colliding particles in tumbling drum system. However, this is not the case for the fluidised bed system due to the large effect of drying in this system. In the fluidised bed systems, no correlation was found between the Sty and the time for coating completion, tc, or the asymptotic Co V, which represents the extent of coating. However, in the tumbling drum system, a correlation was found between Sty and ts; increases in Sty gave a decrease in t-. In summary, this work has shown that the viscosity, collision velocity, the coating thickness and drying are the main parameters which influence the rate and extent of coating via contact spreading.